Key success driver of Japanese elite sport system: Elite athletes' and elite coaches' perspective - Funahashi, H.; Nagamatsu, J.; Shirai, K.; Yamashita, S.; Nakamura, H.; Yamada, E.; Waku, T.; de Bosscher, V.; Mano, Y. (Asian Sport Management Review, 2014)
The purpose of this research was to examine policy-related success drivers leading to athletic success by conducting an evaluation of the elite sport climate with Japanese elite athletes as the survey subjects (n=105). The analysis investigated which specific policy-related factors describe the difference between elite athletes who achieved results in the Top 8 in major international competitions, e.g. World Championships, in the 2 years before the survey was conducted between 19 July 2011 and 31 December 2011 (Elite a) and other elite athletes (Elite ß). The study was drawn from the research framework and scoring system developed by De Bosscher et al. (2006, 2008, 2009, 2010) that is built on the SPLISS (Sports Policy Factors leading to International Sporting Success) model. The results revealed differences in elite sport climate between Elite a and Elite ß in 3 pillars (organisation and structure of sport policies, talent identification and development, and (inter)national competition), which were all evaluated higher by Elite a. The findings support the importance of the improvement of the elite sport climate with the particular reference to the significance of organization and structure of sport policy, talent identification and development, and (inter)national competition.